Management of recurrent urinary tract infections in adults. Issue 6 (June 2017) - Osamwonyi, Barbara; Foley, Charlotte
Abstract: Many women will experience one or more urinary tract infection (UTI) during their life. The most unfortunate will have numerous. They can occur at all ages, and bring significant morbidity and disruption to daily activities. Men presenting with infections, and women with recurrent episodes require further investigation. A diagnosis of a UTI is often based on a typical spectrum of symptoms, with confirmatory urine cultures lagging a few days behind. Unfortunately, symptoms of a UTI may not be typical, and other conditions can manifest similarly. Treatment of UTI with antibiotics is usually required, but there is an increasing awareness of the need for antimicrobial stewardship to avoid the misuse and overuse of antibiotics, even as patients are increasingly reluctant to take them. For patients experiencing recurrent UTI, each recurring infection can be very burdensome yet investigations rarely demonstrate a reversible cause. There are a host of different interventions, both antibiotic and non-antibiotic that aim to reduce the likelihood of further infections, however these are not reliably effective, bring side effects of their own and are often proposed to this desperate population of patients on the back of weak evidence of efficacy.